EDUKASI DAMPAK NEGATIF PENGGUNAAN TAS PUNGGUNG DENGAN BEBAN BERLEBIH TERHADAP KESEHATAN VERTEBRAE PADA SISWA SMA 2 PADANG - Vani, Ade Teti; Melya Susanti; Nadia Purnama Dewi; Rinita Amelia; Dessy Abdullah; Irwan Triansyah; Jefri Henky; Yanti Fitri Yasa; Muhammad Ivan (Nusantara Hasana Journal, 2025)
Carrying a backpack that is excessively heavy can lead to negative effects, including pain in the shoulders, back, and waist. Additionally, it can cause postural changes due to alterations in the shape of the vertebrae. The goal of this Community Service Project (CSP) was to educate students at SMA 2 Padang about the proper use of backpacks, the appropriate weight for backpacks, and the negative effects of carrying overly heavy backpacks on the vertebrae. The method of CSP employed a pre-test and post-test method to measure knowledge retention. Throughout the activity, students received education and vertebral examinations. The key indicators for the CSP were the level of understanding gained regarding backpacks and the effects of excessive weight on vertebral health.The results of CSP indicated a significant increase in knowledge among the students at SMA 2 Padang, with all participants achieving perfect scores of 100 on the post-test. The vertebral examinations did not show any abnormalities, such as kyphosis or scoliosis. The conclusion of CSP successfully enhanced students' understanding of backpack weight and the potential negative impacts of carrying excessive weight on the vertebrae.